Repeatability and reproducibility of pterygium grading based on clinical translucence appearance - Hilmi, Mohd Radzi; Mohd Kamal, Khairidzan; Che Azemin, Mohd Zulfaezal; Abdul Razak, Zulhilmi; Ithnin, Mohd. Hafidz (Acquire Publication, 2021)
Background: The goal of this study was to evaluate the repeatability and reproducibility of pterygium grading based on clinical translucence appearances and its reliability in clinical setting. Methods: A total of 93 primary pterygium eyes from 93 participants who vi sited a tertiary ophthalmic clinic were recruited in this study. Two ( ophthalmologists and two ( optometrists evaluated and graded the 93 primary pterygium images in randomized fashion. Graders were instructed to utilise the clinical translucence appe arance of pterygium to grade them into type I, II and III. Repeatability testing was done by a single expert by comparing grading of each image on two separate sessions, with one month interval between sessions. Reproducibility was tested by comparing the grading obtained by both experts and optometrists. Results: Paired and independent T test results showed no significance difference between graders for both experts and optometrists’ group (all P 0.05). Intra grader and inter grader reliability estimate s were high with intraclass correlation ranging from 0.97 to 0.98 for both groups. Conclusions: Pterygium clinical grading based on its translucence appearance is reliable and repeatable in clinical setting, easily to be graded, interpreted, and recommend ed for clinicians with different levels of experience.